Dieta de Eleutherodactylus binotatus (Spix, 1824) Amphibia, Leptodactylidae) em um fragmento de mata de Belmiro Braga, Zona da Mata, MG, Brasil - Canedo, Clarissa (2002)
Diet studies in anurans have used pre-established concepts, based on anecdotal cases, generally developed in assemblages with similar features. Nevertheless, few authors tested such concepts and classifications. lt is well known that anuran size is correlated to the size of the ingested preys. Many authors suggest that such relation may express differences in size as much as in the sort of ingested preys, since large individuals would be exposed to certain categories of preys unavailable to the smaller individuals. Eleutherodactylus binotatus was chosen to perform this study because it is largely distributed along the Southeastern Brazil, and species of this genus, with direct development, have different size classes occupying the same environment. Comparisons on stomach contents, based on a variety of measurements parameters, were performed between classes in the same season to determine the variation related to size. Data on the same class and different seasons were compared to determined seasonal variation. Selectivity was verified by comparing the proportions of categories in the diet and environment. Eleutherodactylus binotatus adult females may be considered different from the other classes in size but not in sort of ingested item. The mainly seasonal variation was the selectivity to mites and spiders. The former were preferred in the dry season and avoided in the rainy season, whereas the latter were preferred in the rainy season and avoided in the dry season. We conclude Eleutherodactylus binotatus is generalist, despite avoiding consuming ants, as others Leptodactylidae.